Hubungan antara Celebrity Worship dan Fantasy Proneness pada Mahasiswa Penggemar K-Pop - Irene Hilary Manurung; Rahmah Hastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Celebrity worship refers to an excessive psychological attachment to celebrity figures, while fantasy proneness describes an individual’s tendency to become deeply absorbed in imagination. The rapid growth of K-Pop fan communities, or “fandoms” has intensified parasocial interactions with idols, which may influences fans’ fantasy tendencies. This study used a quantitative correlational approach with purposive sampling. Participants were 321 K-Pop fans aged 18 to 25 who were active university students (259 females and 62 males). The Celebrity Attitude Scale (CAS) and the Creative Experiences Questionnaire (CEQ) were used to measure the variables. Spearman’s rho analysis showed a correlation coefficient of r = 0.581 with p = 0.001 < 0.05, indicating a positive and significant relationship between celebrity worship are associated with hugher levels of fantasy proneness. These findings suggest that strong attachment to celebrities may increase individuals’ tendency to engage in fantasy. Theoretically, the results strengthen the understanding of how parasocial relationship influence cognitive processes.